Homozygous Recessive Versican Missense Variation Is Associated With Early Teeth Loss in a Pakistani Family - Bigoni, Stefania; Neri, Marcella; Scotton, Chiara; Farina, Roberto; Sabatelli, Patrizia; Jiang, Chongyi; Zhang, Jianguo; Falzarano, Maria Sofia; Rossi, Rachele; Ognibene, Davide; Selvatici, Rita; Gualandi, Francesca; et al. (Frontiers in Genetics, 2019)
Only a few genes involved in teeth development and morphology are known to be responsible for tooth abnormalities in Mendelian-inherited diseases. We studied an inbred family of Pakistani origin, in which two first-cousin born brothers are affected by early tooth loss with peculiar teeth abnormalities characterized by the absence of cementum formation. Whole exome sequencing revealed a H2665L homozygous mutation in the VCAN gene. Dominant splicing mutations in VCAN are known as causing Wagner syndrome or vitreoretinopathy. In these two patients we explored teeth morphology, while versican expression was assessed by western blot analysis. Early signs of vitreoretinopathy were found in the older brother while parents were completely negative. Our findings suggest that the homozygous recessive H2665L missense mutation genotype impairs the normal morphology of the tooth roots via loss of cementum synthesis, and is also associated with early onset, recessive, Wagner syndrome, thus expanding the phenotype mutation scenario of VCAN mutations.